(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrity and Freedom of Conscience in Preaching the Gospel. From Protestant Reform to Modernity In this paper we are dealing with the period of the Protestant Reformation, a prolific one for the communication of the Gospel, the Puritan period, and the modern period. What has brought the new period of the Reformation, what are the values it promotes and what personalities, what great men of faith have sacrificed their lives to make known to mankind the mystery of Christ are the components of this section. The incursion is continued with the Puritan period, a rather complex one, but like the other periods not without the problem of integrity and even less of religious freedom. The last period treated is that of the modern period. Modernity is a complex concept and it is not the purpose of this paper to discuss it, but only to present events, facts that prove that we are talking about integrity, we are talking about values, but also about religious freedom. The basic idea is that integrity and freedom of conscience are living stones, the cornerstones on which mission and communication, and the preaching of the gospel over time, have been built and are being built.